Ground property characterization by in-situ tests: a report of TC 16 activities - António Viana da Fonseca (2005)
This report presents an overview of the activities undertaken by the ISSMGE Technical Committee TC 16 on in-situtesting during the period from 2001 to 2005, including our terms of reference, membership, website, and the 2nd international conferenceon site characterization (ISC-2004, Porto), as well as other meetings & events.